Urban-rural disparity in the utilization of national community-based hypertension monitoring service—results from the China Health and Retirement Longitudinal Study, 2015 - Song, Hongxun; Feng, Da; Wang, Ruoxi; Tang, Shangfeng; Ghose, Bishwajit; Li, Gang; Chen, Xiaoyu; Feng, Zhanchun (PeerJ, 2019)
Background Since 2009, community-based hypertension monitoring service (CBHMS) has been provided free of charge by the Chinese government as part of the national Essential Public Health Services (EPHS) policy. This study aimed to examine the disparity in the utilization of CBHMS between urban and rural community-dwelling middle-aged and older adults with hypertension. Methods Subjects were 3,479 community-residing hypertensive patients, identified from the China Health and Retirement Longitudinal Study (CHARLS), 2015, a nationally representative survey of Chinese residents aged 45 years and older. The utilization of CBHMS was defined as having one’s blood pressure (BP) examined at least once a season by community or village doctors. Rates of CBHMS use of urban and rural residents with hypertension were compared by using chi-square test. Multiple logistic regression analyses were conducted to examine factors associated with the utilization of CBHMS of hypertensive patients. Results CBHMS was significantly more likely to be used by rural than urban middle-aged and older residents with hypertension (38.6% vs. 25.1%, P < 0.001). Results from multiple logistic regression analyses showed that urban patients who were living in central (OR = 0.37) and western (OR = 0.48) regions (vs. eastern region), had an educational attainment of middle school (OR = 0.33) and college and above (OR = 0.48) (vs. illiterate), and were not taking antihypertensive agents (OR = 0.26) were less likely to use CBHMS, while rural patients who had no medical insurance (OR = 0.56), and were not taking antihypertensive agents (OR = 0.31) were less likely to use CBHMS. Conclusions The national CBHMS is more likely to be used by rural middle-aged and older adults with hypertension in China. The urban-rural difference in the utilization of CBHMS may be resulted from the different demographics of urban and rural middle-aged and older residents and uneven distributions of health services resources between urban and rural areas. Urban-rural disparities in characteristics of CBHMS use should be taken into consideration when promoting the utilization of CBHMS in China.
Keywords: Service utilisation; Urban; Rural; China; Equity; Hypertension monitor